Tuber aestivum, Tuber floridanum e fósforo na produção de mudas de nogueira-pecã - Santos, Darlyng Oliveira (2021)
The pecan tree [Carya illinoinensis (Wangenh) C. Koch, Juglandaceae] has economic importance in several countries, including Brazil, where the most favorable conditions for the development of this crop are found in the South, Southeast and Midwest, regions of soils with low levels of phosphorus, a mineral highly demanded during the initial phase of the pecan tree growth. The pecan tree forms several mutualistic associations with ectomycorrhizal fungi in the soil that result in greater plant growth. This study aimed to obtain information on the use of ectomycorrhizal fungi and phosphorus in the production of pecan seedlings. The experiment was carried out in a greenhouse and the experimental design was completely randomized. The treatments were arranged with four doses of phosphorus (0, 50, 100 and 150 mg.kg-1), two inoculations with ectomycorrhizal fungi (Tuber aestivum and Tuber floridanum) and the control, totaling 12 treatments with five replications. The height of the plants, the stem diameter, the fresh and dry mass of the shoot system and root system, the ectomycorrhizal association and nutrient content in the plant organs were evaluated. The results showed that the inocula of fungi T. aestivum and T. floridanum are capable of colonizing the roots of pecan seedlings. The highest doses of phosphorus under study (100 and 150 mg.kg-1 of P) did not compromise the ectomycorrhizal association of any of the fungal species. Tuber floridanum showed the highest percentage of association with the plant (94.94%). The root length of the seedlings linearly decreased with the increase of P dose. The fresh mass of the shoot system was higher in seedlings with doses of 50 and 150 mg.kg-1 of P. The inoculum T. floridanum showed the highest concentration of P in the roots of seedlings at the dose 50 mg.kg-1. At the dose of 150 mg.kg-1 of P, the highest concentration of P was in the seedlings inoculated with T. aestivum. In the leaves, the highest concentration of P occurred in intermediate doses of P (50 and 100 mg.kg-1 of P) with the inoculum T. floridanum. The dose of 150 mg.kg-1 of P presented the highest concentration of potassium. The plants had lower concentration of manganese at the highest doses of P. The inoculums T. aestivum and T. floridanum are promising in a controlled pecan ectomycorrhization program. The ectomycorrhizal association was not inhibited by the increase of phosphorus doses, however, the intermediate doses 50 and 100 mg.kg-1 of P proved to be more adequate for the seedling growth. The concentration of some nutrients in the plant organs was directly influenced by the inoculums and by the doses of P.